LILRB2/PirB mediates macrophage recruitment in fibrogenesis of nonalcoholic steatohepatitis - Dan-Pei Li; Li Huang; Ran-Ran Kan; Xiao-Yu Meng; Shu-Yun Wang; Hua-Jie Zou; Ya-Ming Guo; Pei-Qiong Luo; Li-Meng Pan; Yu-Xi Xiang; Bei-Bei Mao; Yu-Yu Xie; et al. (Nature Communications, 2023)
Abstract Inhibition of immunocyte infiltration and activation has been suggested to effectively ameliorate nonalcoholic steatohepatitis (NASH). Paired immunoglobulin-like receptor B (PirB) and its human ortholog receptor, leukocyte immunoglobulin-like receptor B (LILRB2), are immune-inhibitory receptors. However, their role in NASH pathogenesis is still unclear. Here, we demonstrate that PirB/LILRB2 regulates the migration of macrophages during NASH by binding with its ligand angiopoietin-like protein 8 (ANGPTL8). Hepatocyte-specific ANGPTL8 knockout reduces MDM infiltration and resolves lipid accumulation and fibrosis progression in the livers of NASH mice. In addition, PirB−/− bone marrow (BM) chimeras abrogate ANGPTL8-induced MDM migration to the liver. And yet, PirB ectodomain protein could ameliorate NASH by sequestering ANGPTL8. Furthermore, LILRB2-ANGPTL8 binding-promoted MDM migration and inflammatory activation are also observed in human peripheral blood monocytes. Taken together, our findings reveal the role of PirB/LILRB2 in NASH pathogenesis and identify PirB/LILRB2-ANGPTL8 signaling as a potential target for the management or treatment of NASH.